2016
DOI: 10.1152/jn.00354.2016
|View full text |Cite
|
Sign up to set email alerts
|

Octopamine stabilizes conduction reliability of an unmyelinated axon during hypoxic stress

Abstract: Mechanisms that could mitigate the effects of hypoxia on neuronal signaling are incompletely understood. We show that axonal performance of a locust visual interneuron varied depending on oxygen availability. To induce hypoxia, tracheae supplying the thoracic nervous system were surgically lesioned and action potentials in the axon of the descending contralateral movement detector (DCMD) neuron passing through this region were monitored extracellularly. The conduction velocity and fidelity of action potentials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Although the direct consequences of hypoxia on spinal motoneurons have not been studied, in vitro examination of orexin neurons from the lateral hypothalamus (Dergacheva et al 2016), the descending contralateral movement detector neuron of the thorax (Money et al 2016), and hippocampal CA1 neurons (Gu and Haddad 2001) confirms that hypoxia also causes reductions in neuronal excitability. This is evident from hyperpolarization, rapid depression of firing rates, and differences in passive properties of the neuron such as changes in resting membrane potential and Na ϩ channel expression (Dergacheva et al 2016;Gu and Haddad 2001;Money et al 2016). However, it must be noted that isolated neuron preparations do not reflect the multitude of factors that can regulate the output of motoneurons.…”
Section: Discussionmentioning
confidence: 96%
“…Although the direct consequences of hypoxia on spinal motoneurons have not been studied, in vitro examination of orexin neurons from the lateral hypothalamus (Dergacheva et al 2016), the descending contralateral movement detector neuron of the thorax (Money et al 2016), and hippocampal CA1 neurons (Gu and Haddad 2001) confirms that hypoxia also causes reductions in neuronal excitability. This is evident from hyperpolarization, rapid depression of firing rates, and differences in passive properties of the neuron such as changes in resting membrane potential and Na ϩ channel expression (Dergacheva et al 2016;Gu and Haddad 2001;Money et al 2016). However, it must be noted that isolated neuron preparations do not reflect the multitude of factors that can regulate the output of motoneurons.…”
Section: Discussionmentioning
confidence: 96%
“…In particular, octopamine plays a major role in olfactory learning and memory formation in the honey bee [ 50 ], important tasks for adapting to different environmental conditions. Interestingly, octopamine has also been shown to be important for stabilizing signaling integrity during hypoxic and thermal stress in other insects [ 82 , 83 ]. The four octopamine receptor genes located within r7 have many fixed differences between highland and lowland bees.…”
Section: Discussionmentioning
confidence: 99%
“…By conducting a whole-genome analysis on mountain forest (A. m. monticola) and savannah (A. m. scutellata) honey bees of Kenya, Wallberg et al (2017) [6] identified an intriguing genomic region (denoted as r7) within the gene octopamine receptor beta-2R (LOC412896) located near a potential chromosomal breakpoint, showing striking variability between A. m. monticola and A. m. scutellata. Octopamine stabilizes hypoxia [24] and hypothermia [25] in locusts. In honey bees, it modulates responses to sucrose [26] and learning odors [27], visuals [28] and nursing [29] behaviors and the thermoregulatory fanning response [30].…”
Section: Introductionmentioning
confidence: 99%